Pre-lithiated negative electrode as well as preparation method and application thereof

By using cocoon-structured lithium carbon materials in the negative electrode of lithium-ion batteries for lithium replenishment, the problem of low Coulombic efficiency for the first time in lithium-ion batteries is solved and the effects of high conductivity, structural stability and long cycle life are achieved.

CN119340392APending Publication Date: 2025-01-21CHINA ENERGY LITHIUM

Patent Information

Application Number
CN202310893885.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

During the first charging and discharging process of existing lithium-ion batteries, the generation of SEI consumes a lot of lithium, resulting in low efficiency for the first time, affecting the actual energy density of the battery and large-scale commercial applications.

Method used

The cocoon-structured lithium carbon material is used as the lithium replenishing agent. The cocoon formed by the structural carbon material is combined with the lithium-containing particles to accurately control the amount of lithium replenishment and improve the conductivity and structural stability of the negative electrode.

Benefits of technology

It significantly improves the first Coulombic efficiency of lithium-ion batteries, extends the cycle life, improves rate performance, and overcomes the shortcomings of lithium supplementation with metallic lithium powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340392A_ABST
    Figure CN119340392A_ABST
Patent Text Reader

Abstract

The invention relates to a pre-lithiation negative electrode and a preparation method and application thereof, the pre-lithiation negative electrode comprises negative electrode active substances and a lithium carbon material with a silkworm cocoon structure, and the lithium carbon material with the silkworm cocoon structure is distributed among the negative electrode active substances. The silkworm cocoon structure includes a cocoon body formed from a structural carbon material and one or more lithium-containing particles contained in the cocoon body. The pre-lithiation negative electrode is stable in structure and controllable in pre-lithiation degree, and when the pre-lithiation negative electrode is matched with a conventional positive electrode for use, the first coulombic efficiency can be remarkably improved, and the cycle life can be remarkably prolonged. The preparation method is simple in process, and large-scale industrial production can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a pre-lithiation negative electrode and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of long cycle life, high energy density, and no memory effect. They are currently the most widely used secondary batteries. At present, the negative electrodes of lithium-ion batteries are commonly made of graphite, silicon-carbon materials, and silicon-oxygen materials. During the first charge and discharge process of lithium-ion batteries, SEI on the negative electrode surface consumes a large amount of lithium, resulting in a low first coulombic efficiency, causing a significant decrease in the actual specific energy of lithium-ion batteries, which seriously restricts the large-scale commercial application of lithium-ion batteries. Therefore, how to improve the first coulombic efficiency has become a research hotspot.

[0003] Some progress has been made in pre-lithiation using metallic lithium powder. Among them, Tesla's patent (CN108780887 B) discloses an electrode membrane comprising: carbon particles, elemental metal and fibrillated binder; wherein the electrode membrane is self-supporting and substantially free of solvent residue. The carbon particles include graphite particles, and the elemental metal includes elemental lithium metal particles. The preparation method comprises combining elemental lithium metal, a plurality of carbon particles and a fibrillated binder to form an electrode membrane mixture; and forming an electrode membrane from the electrode membrane mixture, i.e., pre-lithiation using metallic lithium powder mixed with graphite. Metallic lithium powder is too active and needs to be stabilized before use. A common method is to form a lithium carbonate layer or a lithium fluoride layer on its surface, such as the passivated lithium powder of FMC, but the lithium carbonate layer or the lithium fluoride layer has a low conductivity, and the metallic lithium powder forms voids in the negative electrode after taking effect, which not only reduces the conductivity of the negative electrode, but also may grow lithium dendrites in the thinner area of ​​the negative electrode, which is not conducive to the improvement of the negative electrode performance.

[0004] How to develop a negative electrode that can accurately control the amount of lithium replenishment, has a stable structure after pre-lithiation, does not significantly reduce conductivity, and inhibits dendrite growth has become an urgent problem that needs to be solved at this stage. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a pre-lithiation negative electrode and a preparation method and use thereof. The pre-lithiation negative electrode selects a lithium-carbon material with a cocoon structure as a lithium supplement, which significantly improves the first coulombic efficiency of a lithium-ion battery. The lithium-carbon material with a cocoon structure contains a structural carbon material with good conductivity and certain rigidity, which can improve the conductivity and structural stability of the pre-lithiation negative electrode.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a pre-lithiation negative electrode, the pre-lithiation negative electrode comprising a negative electrode active material and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the negative electrode active material;

[0008] The cocoon structure includes a cocoon body formed of a structural carbon material and one or more lithium-containing particles contained in the cocoon body.

[0009] In the present invention, a lithium-carbon material with a cocoon structure is used to replenish lithium, and lithium-containing particles are used as a lithium source to accurately replenish lithium for the negative electrode. The cocoon structure formed by the structural carbon material has a certain rigidity, and has good contact with the negative electrode active material. It plays a supporting role and constructs an electronic path at the same time. Even after the lithium-containing particles are consumed, no obvious voids will be formed, and the internal resistance of the negative electrode will not be increased. At the same time, it also has a good lithium ion path, which improves the ion conductivity of the pre-lithiation negative electrode and can meet the needs of high-rate charge and discharge; the structural carbon material cocoon structure can also absorb and retain electrolyte, so that the lithium-containing particles can give full play to their capacity, and overcome the defects of metal lithium powder replenishing lithium. The pre-lithiation negative electrode has the advantages of high structural stability, long cycle life and good rate performance.

[0010] Optionally, the negative electrode active material includes graphite, tin-based materials, hard carbon, soft carbon, activated carbon, mesophase carbon microspheres, silicon carbon (Si / C) materials or silicon oxygen (SiO x (0<x≤2)) Any one or a combination of at least two of the materials.

[0011] Optionally, the structural carbon material includes any one or a combination of at least two of granular, linear or flaky nanocarbon materials, preferably acetylene black, Ketjen black, Cabot BP2000, Super P, single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, doped carbon nanotubes, graphene, doped graphene, carbon nanofibers or doped carbon nanofibers, preferably any one or a combination of at least two of single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, doped carbon nanotubes, graphene or doped graphene.

[0012] Optionally, the doping elements in the doped carbon nanotubes, doped graphene or doped carbon nanofibers independently include any one of fluorine, nitrogen, oxygen, phosphorus, silver, silicon, tin or zinc, or a combination of at least two of them.

[0013] Optionally, the lithium-containing particles include metallic lithium particles and / or metallic lithium alloy particles, preferably metallic lithium alloy particles. A small amount of the metallic lithium alloy particles remain after lithium replenishment to form a skeleton, which cooperates with the structural carbon material and does not produce large voids in the negative electrode, thereby increasing the internal resistance of the negative electrode. At the same time, the deposition of metallic lithium can be regulated to improve the cycle performance of the negative electrode while achieving lithium replenishment.

[0014] Optionally, the mass content of metallic lithium in the metallic lithium alloy particles is not less than 70%, for example, it can be 70%, 72%, 75%, 80%, 83%, 85%, 88%, 90%, 93%, 95%, 97% or 99%, etc., including but not limited to the listed point values. If the mass content is too low, more inactive lithium substances will be introduced, affecting the energy density of the negative electrode, and preferably it is not less than 85%.

[0015] Optionally, the average particle size of the lithium-containing particles is 1-100 microns, for example, 1 micron, 3 microns, 5 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 40 microns, 50 microns, 60 microns, 70 microns, 80 microns, 90 microns or 100 microns, including but not limited to the listed point values, preferably 5-30 microns.

[0016] Optionally, the metallic lithium alloy particles include binary lithium alloys and / or ternary lithium alloys, the binary lithium alloy powder includes any one of lithium magnesium alloys, lithium boron alloys, lithium silver alloys, lithium indium alloys, lithium silicon alloys, lithium aluminum alloys or lithium tin alloys, or a combination of at least two of them; the ternary lithium alloy powder includes any one of lithium tin silver alloys, lithium silver silicon alloys or lithium boron zinc alloys, or a combination of at least two of them.

[0017] Optionally, the mass ratio of the structural carbon material to the lithium-containing particles is 1:(1-1000), for example, 1:1, 1:5, 1:10, 1:20, 1:50, 1:55, 1:60, 1:80, 1:90, 1:100, 1:120, 1:150, 1:200, 1:300, 1:400, 1:450, 1:480, 1:500, 1:550, 1:600,

[0018] 1:700, 1:800, 1:900, 1:950 or 1:1000, etc., including but not limited to the said point values, preferably 1:(10-500).

[0019] Optionally, an organic conductive layer is provided between the lithium-containing particles and the structural carbon material, and the organic conductive layer includes an organic lithium ion conductive agent and a conductive agent. The organic conductive layer is conducive to the diffusion of lithium ions, and further improves the ionic conductivity of the pre-lithiation negative electrode.

[0020] The conductive agent includes at least one of carbon nanotubes, carbon black, graphene, and acetylene black. The organic lithium ion conductive agent includes polyethylene oxide, polyethylene glycol, polysiloxane, polytrimethylene carbonate, polycarbonate, polyethylene carbonate, polypropylene carbonate, polyvinylene carbonate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, poly(vinylidene fluoride-hexafluoropropylene), polyphenylene sulfide, p-benzoquinone, and a copolymer or mixture of at least two of the above polymers.

[0021] The mass ratio of the lithium-containing particles, the organic lithium ion transport agent and the conductive agent is (80-95): (1-10): (0.1-10), preferably (90-95): (5-10) (0.5-5).

[0022] Optionally, the mass ratio of the negative electrode active material to the lithium-carbon material with a cocoon structure includes but is not limited to 1g:(1-300)mg, for example, it can be 1g:1mg, 1g:3mg, 1g:5mg, 1g:10mg, 1g:15mg, 1g:20mg, 1g:30mg, 1g:50mg, 1g:100mg, 1g:120mg, 1g:150mg, 1g:180mg, 1g:200mg, 1g:240mg or 1g:300mg, etc., including but not limited to the point values. The mass ratio can be selected according to the type of negative electrode active material, the type of lithium-carbon material with a cocoon structure, the first coulomb efficiency and actual needs. Generally, the first coulomb efficiency of graphite negative electrode material is higher than that of silicon-containing negative electrode material. For the same type of lithium-carbon material with a cocoon structure, the actual demand for graphite negative electrode material is smaller, preferably 1g:(10-200)mg. When the mass ratio is too small, that is, when the mass of the lithium-carbon material in the cocoon structure is relatively large, the pre-lithiation negative electrode not only has the effect of pre-lithiation, but also has the function of storing lithium sources, showing the characteristics of a composite negative electrode. During the battery cycle, the lithium source can be continuously replenished, further improving the cycle performance and energy density of the pre-lithiation negative electrode.

[0023] In a second aspect, the present invention provides a method for preparing a pre-lithiation negative electrode as described in the first aspect, the method comprising the following steps:

[0024] (1) mixing a structural carbon material, lithium-containing particles and an organic solvent, and then spray drying or stirring at a rotation speed of more than 5000 rpm to obtain a lithium-carbon material with a cocoon structure;

[0025] (2) mixing the negative electrode active material, the conductive agent and the first binder, and then fiberizing the binder to obtain a first mixture, and then mixing the first mixture with a lithium-carbon material with a cocoon structure to obtain a second mixture, hot pressing the second mixture into a negative electrode active material layer, and then compounding it with a current collector to obtain the pre-lithiation negative electrode;

[0026] Alternatively, the negative electrode active material, the conductive agent, the second binder, the cocoon-structured lithium-carbon material and the organic solvent are mixed to prepare a negative electrode slurry, and then the negative electrode slurry is coated on the surface of the current collector to obtain the pre-lithiation negative electrode.

[0027] In the present invention, regardless of whether a dry method (without using an organic solvent) or a wet method (using an organic solvent) is used, a cocoon-structured lithium-carbon material can be used as a lithium source, and it can be mixed into the electrode system during the mixing process to directly prepare a pre-lithiated negative electrode. Preferably, the dry method is used to prepare a pre-lithiated negative electrode. The dry method can prepare a high energy density negative electrode and the morphology of the cocoon-structured lithium-carbon material is kept better.

[0028] Optionally, step (1) further comprises the following operations: (a) mixing lithium-containing particles, an organic lithium ion transport agent and a conductive agent to form particles consisting of lithium-containing particles and an organic conductive layer coated on the surface thereof;

[0029] (b) uniformly mixing the obtained particles with the structural carbon material in an organic solvent, and then spray drying or high-speed stirring to obtain a lithium-carbon material with a cocoon structure. The operation constructs an organic ion conductive layer on the surface of the lithium-containing particles, which is conducive to the diffusion of lithium ions and further improves the ionic conductivity of the pre-lithiation negative electrode.

[0030] Alternatively, the mixing of the lithium-containing particles, the organic lithium ion transport agent and the conductive agent can be carried out in the presence of an organic solvent, and then the solvent is removed. The organic solvent can include N-methylpyrrolidone (NMP), ethanol, n-hexane, liquid paraffin, tetrahydrofuran, p-xylene, etc.

[0031] Optionally, the organic solvent in step (1) is any one of N-methylpyrrolidone, liquid alkane with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof.

[0032] Optionally, the spray drying conditions in step (1) include: an air inlet temperature of 180-240°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 215°C or 220°C, etc., preferably 200-220°C; an air outlet temperature of 90-110°C, for example, 90°C, 95°C, 100°C, 105°C or 110°C, etc., preferably 100-110°C; and an atomization pressure of 0.1-0.5Mpa, for example, 0.2Mpa, 0.25Mpa, 0.3Mpa, 0.35Mpa or 0.4Mpa, etc., preferably 0.2-0.4Mpa.

[0033] Optionally, the speed of the high-speed stirring in step (1) is 6000-15000rpm, and the time is 0.5-10min. For example, the speed can be 6000rpm, 6500rpm, 7000rpm, 75000rpm, 8000rpm, 8500rpm, 9000rpm, 10000rpm, 11000rpm, 11500rpm, 12000rpm, 12500rpm, 13000rpm, 14000rpm, 14500rpm or 15000rpm, and the time can be 0.5min, 1min, 1.5min, 2min, 2.5min, 3min, 3.5min, 4min, 4.5min, 5min, 6min, 7min, 8min, 9min, 9.5min or 10min, etc., and the preferred speed is 8000-12000rpm, and the time is 1-5min.

[0034] Optionally, in step (2), the first binder includes any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyisobutylene, polytetrafluoroethylene or sodium carboxymethyl cellulose, or a combination of at least two thereof.

[0035] Optionally, the organic solvent in step (2) comprises any one or a combination of at least two of N-methylpyrrolidone, liquid alkanes with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, preferably any one or a combination of at least two of p-xylene, n-hexane or heptane.

[0036] In the present invention, the type of the conductive agent is not specifically limited, and the conductive agent includes but is not limited to any one or a combination of at least two of acetylene black, Ketjen black, conductive graphite, Cabot black or Super P. As long as it is a type commonly used by those skilled in the art, it can be used in the present invention.

[0037] In the present invention, the type of binder is not specifically limited, and the second binder includes, but is not limited to, any one or a combination of at least two of polyvinylidene fluoride, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer, or styrene-ethylene-butylene-styrene block copolymer. As long as it is a type commonly used by those skilled in the art, it can be used in the present invention.

[0038] Optionally, the mass ratio of the conductive agent, the first binder or the second binder and the negative electrode active material is (1-10): (1-10): (80-98), preferably (2-5): (2-5): (90-96).

[0039] As a preferred technical solution of the present invention, the steps for preparing the negative electrode slurry in step (2) are as follows:

[0040] (a) mixing a negative electrode active material, a conductive agent, a second binder and an organic solvent for a primary mixing, and then adding a lithium carbon material with a cocoon structure for secondary mixing to prepare a negative electrode slurry;

[0041] The secondary mixing time is 30-60 min, and the secondary mixing speed is 3000-5000 rpm; the mixing time can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc., and the speed can be 3000 rpm, 3200 rpm, 3500 rpm, 4000 rpm, 4500 rpm, 4800 rpm or 5000 rpm, etc. The mixing time and speed include but are not limited to the listed point values, and are adjusted according to the actual process.

[0042] (b) coating the negative electrode slurry on the surface of the current collector to obtain the pre-lithiation negative electrode.

[0043] In a third aspect, the present invention provides an energy storage device, wherein the energy storage device comprises the pre-lithiation negative electrode as described in the first aspect above.

[0044] Optionally, the energy storage device includes but is not limited to a lithium ion battery and / or a lithium ion supercapacitor.

[0045] Compared with the prior art, the present invention has at least one of the following beneficial effects:

[0046] (1) The pre-lithiation negative electrode provided by the present invention adopts a lithium-carbon material with a cocoon structure as a lithium supplement, which is evenly mixed with the negative electrode active material and has good contact, and does not form obvious voids in the negative electrode to increase the internal resistance. The pre-lithiation negative electrode has a high first coulombic efficiency and structural stability;

[0047] (2) The present invention further improves the initial coulombic efficiency and cycle performance of the pre-lithiation negative electrode by selecting the type of lithium-containing particles and regulating parameters such as the mass ratio of lithium-carbon material to lithium-containing particles;

[0048] (3) The preparation method provided by the present invention is simple to operate and has high production efficiency. In particular, the coating process is different from the existing process, and the solvent and binder used are friendly to metallic lithium, providing a new idea for accurate lithium replenishment of the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is a schematic diagram of a pre-lithiation negative electrode of the present invention;

[0050] Figure 2 This is a SEM image of the silkworm cocoon structure lithium carbon material of Example 4;

[0051] Figure 3is a cross-sectional SEM image of the pre-lithiation negative electrode in Example 4;

[0052] 1-current collector, 2-negative electrode active material, 3-lithium-carbon material with cocoon structure. DETAILED DESCRIPTION

[0053] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0054] For example, the present invention provides a pre-lithiation negative electrode, the schematic diagram of the pre-lithiation negative electrode is as follows Figure 1 The pre-lithiation negative electrode comprises a current collector 1, on the surface of which a negative electrode active material 2 and a lithium carbon material 3 with a cocoon structure are arranged, wherein the lithium carbon material 3 with a cocoon structure is distributed between the negative electrode active materials 2 and is evenly mixed, and wherein the lithium carbon material with a cocoon structure comprises a cocoon body formed by a structural carbon material and one or more lithium-containing particles contained in the cocoon body (refer to Figure 2 As shown in the SEM image, the cocoon is in good contact with the negative electrode active material 2, constructing a good electron path. After lithium replenishment, no obvious voids will be formed in the negative electrode, thereby increasing the internal resistance. The pre-lithiation negative electrode has a higher first coulombic efficiency and structural stability.

[0055] Example 1

[0056] This embodiment provides a pre-lithiation negative electrode, which includes graphite and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the graphite.

[0057] The method for preparing the pre-lithiation negative electrode comprises the following steps:

[0058] (1) Graphene (XF001W 7440-44-0, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), multi-walled carbon nanotubes (XFM01 1333-86-4, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), Cabot BP2000, metal lithium powder with an average particle size of 5 μm and n-hexane were mixed, and the mass ratio of the total mass of graphene, multi-walled carbon nanotubes and Cabot BP2000 to the metal lithium powder was 1:1000, and then high-speed dispersion was performed at a rotation speed of 5000 rpm for 10 minutes to obtain a lithium-carbon material with a cocoon structure;

[0059] (2) Graphite, acetylene black, and styrene-butadiene rubber (SBR, 1502, Sinopec Jilin Chemical) were mixed in quantities of 800 g, 100 g, and 100 g, with n-hexane as the solvent, to prepare a first slurry, and then 8 g of a lithium-carbon material with a cocoon structure was added, and the mixture was stirred at a speed of 3000 rpm for 60 min to obtain a second slurry, and then the second slurry was coated on a surface of a 6 μm carbon-coated copper foil and dried to obtain the pre-lithiation negative electrode.

[0060] Example 2

[0061] The present embodiment provides a pre-lithiation negative electrode, wherein the pre-lithiation negative electrode comprises silicon carbon and a lithium carbon material with a cocoon structure, wherein the lithium carbon material with a cocoon structure is distributed between the silicon carbon.

[0062] The method for preparing the pre-lithiation negative electrode comprises the following steps:

[0063] (1) acetylene black, polyethylene oxide (Aladdin, P432440) and metal lithium powder are mixed in p-xylene in a mass ratio of 5:5:90, and the p-xylene is removed by drying to form metal lithium powder containing an organic conductive layer;

[0064] (2) mixing single-walled carbon nanotubes, metal lithium powder with an average particle size of 45 μm and an organic conductive layer, and n-hexane, wherein the mass ratio of the single-walled carbon nanotubes to the metal lithium powder is 1:500, and then dispersing at a high speed of 8000 rpm for 8 minutes to obtain a lithium-carbon material with a cocoon structure;

[0065] (3) Silicon carbon (Bai Te Rui, DXB8), carbon fiber, and polyvinylidene fluoride (Su Wei, 5130) were mixed in masses of 800g, 100g, and 100g, with N-methylpyrrolidone as the solvent, to prepare a first slurry, and then 160g of lithium carbon material with a cocoon structure was added, and stirred at a speed of 4500rpm for 45min to obtain a second slurry, and then the second slurry was coated on the surface of 6μm carbon nanotube paper and dried to obtain the pre-lithiation negative electrode.

[0066] Example 3

[0067] This embodiment provides a pre-lithiation negative electrode, which includes silicon oxygen and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the silicon oxygen.

[0068] The method for preparing the pre-lithiation negative electrode comprises the following steps:

[0069] (1) carbon nanofibers (Aladdin, C478418), conductive graphite KS-6, lithium-magnesium alloy particles with an average particle size of 100 μm (magnesium mass fraction of 10%) and p-xylene are mixed, and the mass ratio of the total mass of single-walled carbon nanotubes and conductive carbon black to the metal lithium powder is 1:100, and then high-speed dispersion is carried out at a speed of 12000 rpm for 5 minutes to obtain a lithium-carbon material with a cocoon structure;

[0070] (2) Silicon oxide (Bai Te Rui, DXA5), Super P, and polyisobutylene (Aladdin, P418837) were mixed in masses of 800g, 100g, and 100g, with heptane as the solvent, to prepare a first slurry, and then 240g of lithium-carbon material with a cocoon structure was added, and stirred at a speed of 4500rpm for 45min to obtain a second slurry, and then the second slurry was coated on the surface of a 6μm perforated copper foil and dried to obtain the pre-lithiation negative electrode.

[0071] Example 4

[0072] This embodiment provides a pre-lithiation negative electrode, which includes graphite and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the graphite.

[0073] The method for preparing the pre-lithiation negative electrode comprises the following steps:

[0074] (1) Single-walled carbon nanotubes (XFS02 1333-86-4, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), metal lithium powder with an average particle size of 50 μm and n-hexane were mixed, and the mass ratio of the single-walled carbon nanotubes to the metal lithium powder was 1:500, and then spray-dried, with an inlet air temperature of 220° C., an outlet air temperature of 100° C., and an atomization pressure of 0.5 MPa to obtain a lithium-carbon material with a cocoon structure; the SEM characterization of the lithium-carbon material with a cocoon structure is as follows: Figure 2 As shown in the figure, it can be clearly seen that the single-walled carbon nanotubes are wrapped around the surface of the metal lithium powder to form a cocoon body, and the cocoon body contains the metal lithium powder to form a lithium-carbon material with a cocoon structure;

[0075] (2) Graphite, acetylene black, and polytetrafluoroethylene were mixed in weights of 900 g, 50 g, and 50 g, and then processed by ultra-strong shearing equipment to fiberize the polytetrafluoroethylene binder. 180 g of lithium-carbon material with a silkworm cocoon structure was added, and a 120 μm thick negative electrode film was obtained by extrusion rolling at 80° C. The negative electrode film was composited with a carbon-coated copper foil by hot pressing to obtain the pre-lithiation negative electrode. The cross-sectional SEM characterization of the pre-lithiation negative electrode is as follows: Figure 3 As shown in the figure, it can be clearly seen that the cocoon-structured lithium-carbon material (the part marked in the black circle in the figure) is evenly distributed between materials such as graphite (the part marked outside the black circle in the figure), and a good cocoon structure can be maintained.

[0076] Example 5

[0077] Compared with Example 4, the only difference is that the mass of the cocoon-structured lithium-carbon material in step (2) is replaced with 0.9 g, and the other conditions are the same.

[0078] Example 6

[0079] Compared with Example 4, the only difference is that the mass of the cocoon-structured lithium-carbon material in step (2) is replaced with 300 g, and the other conditions are the same.

[0080] Example 7

[0081] Compared with Example 4, the only difference is that the metallic lithium powder in step (1) is replaced by lithium-indium alloy powder, the mass fraction of indium is 20%, and the other conditions are the same.

[0082] Comparative Example 1

[0083] Compared with Example 4, the only difference is that the cocoon-structured lithium-carbon material in step (2) is replaced by the metallic lithium powder in step (1), and the other conditions remain unchanged.

[0084] Comparative Example 2

[0085] Compared with Example 4, the only difference is that the lithium-carbon material with a cocoon structure is not added in step (2), and the other conditions remain unchanged.

[0086] Comparative Example 3

[0087] Compared with Example 4, the only difference is that the rotation speed in step (1) is replaced with 2000 rpm, and the other conditions remain unchanged. At the rotation speed, the single-walled carbon nanotubes can be fully mixed with the metal lithium powder, but no cocoon structure is formed.

[0088] Negative electrode performance test:

[0089] The negative electrodes of Examples 1-7 and Comparative Examples 1-3 were assembled into soft-pack batteries with nickel cobalt manganese oxide positive electrodes for testing. The first coulombic efficiency and cycle test data at 0.2C are shown in Table 1 below.

[0090] Table 1

[0091]

[0092] From Table 1, we can see that:

[0093] (1) Based on Examples 4-6, it can be seen that the degree of pre-lithiation is closely related to the amount of cocoon-structured lithium-carbon material used. When the amount is small (Example 5), the improvement of the first coulombic efficiency and cycle performance is not obvious; when the amount is too much (Example 6), the first coulombic efficiency and cycle performance are significantly improved, but it is not conducive to the preparation of a high energy density battery.

[0094] (2) Combining Example 4 and Example 7, it can be seen that the first coulombic efficiency of the battery corresponding to Example 4 is close to that of Example 7, and the cycle performance is worse than that of Example 7. This is because lithium indium alloy is used for lithium supplementation in Example 7. Indium can regulate the deposition of metallic lithium and conduct electrons at the same time, cooperating with the structural carbon material single-walled carbon nanotubes, so that the negative electrode exhibits excellent cycle performance.

[0095] (3) Based on Example 4 and Comparative Examples 1-3, it can be seen that when the same mass of lithium supplement is added, the pre-lithiation agents with different structures have different degrees of improvement in the initial coulombic efficiency of the negative electrode and the improvement in the cycle performance. The core-shell structured lithium-carbon material of the present invention is used as a lithium supplement. The cocoon-structured lithium-carbon material contains a structural carbon material with good conductivity and a certain rigidity, which can improve the conductivity and structural stability of the pre-lithiation negative electrode, so that the pre-lithiation negative electrode has a higher initial coulombic efficiency and excellent cycle performance.

[0096] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A pre-lithiation negative electrode, characterized in that: The pre-lithiation negative electrode comprises a negative electrode active material and a lithium-carbon material with a cocoon structure, wherein the lithium-carbon material with a cocoon structure is distributed between the negative electrode active material; The cocoon structure includes a cocoon body formed of a structural carbon material and one or more lithium-containing particles contained in the cocoon body.

2. The pre-lithiation negative electrode according to claim 1, characterized in that The negative electrode active material includes any one or a combination of at least two of graphite, tin-based materials, hard carbon, soft carbon, activated carbon, mesophase carbon microspheres, silicon-carbon materials or silicon-oxygen materials; The structural carbon material is any one or a combination of at least two of granular, linear or flaky nanocarbon materials, and the structural carbon material includes any one or a combination of at least two of acetylene black, Ketjen black, Cabot BP2000, Super P, single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, doped carbon nanotubes, graphene, doped graphene, carbon nanofibers or doped carbon nanofibers; The doping elements in the doped carbon nanotubes, doped graphene or doped carbon nanofibers independently include any one of fluorine, nitrogen, oxygen, phosphorus, silver, silicon, tin or zinc, or a combination of at least two of them.

3. The pre-lithiation negative electrode according to claim 1, characterized in that The lithium-containing particles include metal lithium particles and / or metal lithium alloy particles, and the mass content of metal lithium in the metal lithium alloy particles is not less than 70%; Wherein, the average particle size of the lithium-containing particles is 1-100 microns; Among them, the metallic lithium alloy particles include binary lithium alloy and / or ternary lithium alloy, the binary lithium alloy powder includes any one of lithium magnesium alloy, lithium boron alloy, lithium silver alloy, lithium indium alloy, lithium silicon alloy, lithium aluminum alloy or lithium tin alloy, or a combination of at least two of them; the ternary lithium alloy powder includes any one of lithium tin silver alloy, lithium silver silicon alloy or lithium boron zinc alloy, or a combination of at least two of them.

4. The pre-lithiation negative electrode according to claim 1, characterized in that The cocoon structure further comprises an organic conductive layer disposed between the lithium-containing particles and the structural carbon material, wherein the organic conductive layer comprises an organic ion conductive agent and a conductive agent; The conductive agent comprises at least one of carbon nanotubes, carbon black, graphene and acetylene black; The organic lithium ion transport agent includes polyethylene oxide, polyethylene glycol, polysiloxane, polytrimethylene carbonate, polycarbonate, polyethylene carbonate, polypropylene carbonate, polyvinylene carbonate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, poly(vinylidene fluoride-hexafluoropropylene), polyphenylene sulfide, para-benzoquinone, and a copolymer or mixture of at least two of the above polymers.

5. The pre-lithiation negative electrode according to claim 1, characterized in that The mass ratio of the negative electrode active material to the lithium carbon material with a cocoon structure is 1g:(1-300)mg; The mass ratio of the structural carbon material to the lithium-containing particles is 1:(1-1000).

6. A method for preparing a pre-lithiated negative electrode as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) mixing a structural carbon material, lithium-containing particles and an organic solvent, and then spray drying or stirring at a rotation speed of more than 5000 rpm to obtain a lithium-carbon material with a cocoon structure; (2) mixing the negative electrode active material, the conductive agent and the first binder, and then fiberizing the binder to obtain a first mixture, and then mixing the first mixture with a lithium-carbon material with a cocoon structure to obtain a second mixture, hot pressing the second mixture into a negative electrode active material layer, and then compounding it with a current collector to obtain the pre-lithiation negative electrode; Alternatively, the negative electrode active material, the conductive agent, the second binder, the cocoon-structured lithium-carbon material and the organic solvent are mixed to prepare a negative electrode slurry, and then the negative electrode slurry is coated on the surface of the current collector to obtain the pre-lithiation negative electrode.

7. The method according to claim 6, characterized in that The organic solvent in step (1) is any one of N-methylpyrrolidone, liquid alkane with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof.

8. The method according to claim 6, characterized in that In step (2), the first binder includes any one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polytetrafluoroethylene or sodium carboxymethyl cellulose, or a combination of at least two thereof; The organic solvent in step (2) includes any one of N-methylpyrrolidone, liquid alkanes with 5 to 10 carbon atoms, benzene, p-xylene or petroleum ether, or a combination of at least two thereof; The conductive agent in step (2) includes any one of acetylene black, Ketjen black, conductive graphite, Cabot black or Super P, or a combination of at least two thereof; In step (2), the second binder comprises any one of polyvinylidene fluoride, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer or styrene-ethylene-butylene-styrene block copolymer, or a combination of at least two thereof; The mass ratio of the conductive agent, the first binder or the second binder and the negative electrode active material is (1-10): (1-10): (80-98).

9. The method according to claim 6, characterized in that The steps for preparing the negative electrode slurry in step (2) are as follows: (a) mixing a negative electrode active material, a conductive agent, a second binder and an organic solvent for a primary mixing, and then adding a lithium carbon material with a cocoon structure for secondary mixing to prepare a negative electrode slurry; The secondary mixing time is 30-60 min, and the secondary mixing speed is 3000-5000 rpm; (b) coating the negative electrode slurry on the surface of the current collector to obtain the pre-lithiation negative electrode.

10. An energy storage device, characterized in that: The energy storage device comprises the pre-lithiation negative electrode as described in any one of claims 1-5.

Citation Information

Patent Citations

  • A mixture of elemental metals and carbon for energy storage devices

    CN108780887B

Cited By

  • Pre-lithiated silicon-carbon negative electrode, negative electrode plate, secondary battery and preparation method of pre-lithiated silicon-carbon negative electrode

    CN120497302A